(untitled) (Research, Society and Development, 2024)
Diabetes Mellitus (DM) is a multifactorial disease, including peripheral resistance, associated with higher rates of hospitalizations, incidence of cardiovascular and cerebrovascular diseases, blindness, renal failure and non-traumatic amputations. It is estimated that the global affected population is expected to reach 471 million in 2035. The objective of this article is to present a bibliographic review study that seeks to elucidate the therapeutic use of liraglutide in the treatment of DM, considering mechanisms of action in the physiology of the disease and discussing the physiological impacts of the use of liraglutide on the body. This is a narrative review in the PUBMED and SciELO databases of systematic reviews and meta-analyses from 2010 to 2024, using the keywords: “Liraglutide”; “Diabetes Mellitus”; “Drug Therapy”, with free full text that addresses the topic sought. Liraglutide is an incretinomimetic drug, which increases insulin secretion by pancreatic beta cells, decreases glucagon secretion, delays gastric emptying and decreases appetite. In addition to glycemic control, liraglutide has a significant effect on reducing body weight. The long-term safety of liraglutide in association with neoplasms is reported to be rare and continues to be studied. It appears, therefore, that GLP-1 analogues have a multifaceted role in the treatment of DM2. Despite optimism, new studies are awaited to rule out unfavorable implications for human health.